2018
DOI: 10.3389/fnagi.2018.00305
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Biomarkers for Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is one of the common progressive neurodegenerative disorders with several motor and non-motor symptoms. Most of the motor symptoms may appear at a late stage where most of the dopaminergic neurons have been already damaged. In order to provide better clinical intervention and treatment at the onset of disease, it is imperative to find accurate biomarkers for early diagnosis, including prodromal diagnosis and preclinical diagnosis. At the same time, these reliable biomarkers can also be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
135
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(140 citation statements)
references
References 221 publications
(248 reference statements)
1
135
0
4
Order By: Relevance
“…In fact, despite several years of research focused on the identification of potential molecular biomarkers of neurodegenerative diseases, there is no biochemical diagnostic model that helps in the diagnosis of those diseases, including PD [51]. Moreover, critical reviews regarding the potential candidates highlighted so far, have reduced the list of best candidates to a few molecules that have already a known link to the PD pathogenesis and other neurodegenerative diseases, such as the protein DJ-1, oligomerized αsynuclein, tau, phospho-tau, amyloid β1-42 [for concise reviews on this topic consult [5,6,51]]. This evidence further confirms the importance of including the biological relevance as a selection criterion in the biomarker discovery pipelines, as it was introduced in this work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, despite several years of research focused on the identification of potential molecular biomarkers of neurodegenerative diseases, there is no biochemical diagnostic model that helps in the diagnosis of those diseases, including PD [51]. Moreover, critical reviews regarding the potential candidates highlighted so far, have reduced the list of best candidates to a few molecules that have already a known link to the PD pathogenesis and other neurodegenerative diseases, such as the protein DJ-1, oligomerized αsynuclein, tau, phospho-tau, amyloid β1-42 [for concise reviews on this topic consult [5,6,51]]. This evidence further confirms the importance of including the biological relevance as a selection criterion in the biomarker discovery pipelines, as it was introduced in this work.…”
Section: Discussionmentioning
confidence: 99%
“…4 Centro Hospitalar Cova da Beira, E.P.E, Covilhã, Portugal. 5 Neurology Department, Centro Hospitalar e Universitário de Coimbra, Coimbra, Portugal. 6 Coimbra Institute for Biomedical Imaging and Translational Research (CIBIT), Coimbra, Portugal.…”
Section: Supplementary Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is necessary to find a robust biomarker test for early diagnosis. It has been reported that combination of biochemical biomarkers, neuroimaging and genetic screening are necessary for the early and accurate diagnosis of neurodegenerative diseases, such as Alzheimer's disease (AD) and Parkinson's disease [28][29][30]. Although genetic testing was strongly recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Research has explored a number of potential molecular markers for PD that center on measures that directly or indirectly assess the degree of mitochondrial dysfunction, oxidative stress, Lewy bodies formation, neuroinflammation, and other core pathological characteristics of PD in readily accessible biofluids or biopsies (62). Their utility in diagnosing or prognosing the disease early on, however, has remained limited (63,64).…”
Section: Molecular Markers Of Parkinson's Diseasementioning
confidence: 99%